The stereotypical representation of women in the classic fairy tales Snow White, Cinderella, and Sleeping Beauty - Anisa Dyah Berlianti (Indonesian Journal of Social Sciences, 2021)
The stereotype that emerges from some classic fairy tales is a princess who has a beautiful face and an angelic heart, a prince on a white horse who is handsome and charming, and a happy ending forever. These three sweet things are generally always the main menu served in bedtime fairy tales, including the classic fairy tales Snow White, Cinderella, and Sleeping Beauty. Besides sounding beautiful, the plot and characterization presented in the classic fairy tale represent a woman through feminine standards packaged through stereotypes. This research uses qualitative research methods and narrative analysis. The research results found details of the seven functional characters of the characters in the fairy tale. It can then be seen that various stereotypical representations aimed at women in the three tales, ranging from the obsession with natural beauty, misconceptions about the meaning of ambition, and marriage, are the solution for all the problems of a woman.